2014
DOI: 10.1111/cobi.12238
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the Cost of Keeping Options Open for Conservation in a Changing Climate

Abstract: Policy documents advocate that managers should keep their options open while planning to protect coastal ecosystems from climate-change impacts. However, the actual costs and benefits of maintaining flexibility remain largely unexplored, and alternative approaches for decision making under uncertainty may lead to better joint outcomes for conservation and other societal goals. For example, keeping options open for coastal ecosystems incurs opportunity costs for developers. We devised a decision framework that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Evaluating the environmental impact of projects is a critical prerequisite for sustainable development. Anticipating and acting on foreseeable development-conservation conflicts helps cost-effectively reduce biodiversity losses because the cost of conserving species and communities increases rapidly as they become less widespread and options for their conservation narrow (Mills et al 2014). In many countries, existing legislation and regulation requires formal assessment of activities deemed likely to pose some risk to threatened species (Chaker et al 2006;Connelly 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the environmental impact of projects is a critical prerequisite for sustainable development. Anticipating and acting on foreseeable development-conservation conflicts helps cost-effectively reduce biodiversity losses because the cost of conserving species and communities increases rapidly as they become less widespread and options for their conservation narrow (Mills et al 2014). In many countries, existing legislation and regulation requires formal assessment of activities deemed likely to pose some risk to threatened species (Chaker et al 2006;Connelly 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the tools we described have been tested in environmental contexts (e.g., using large‐magnitude, broad‐bracket frames to increase the attractiveness of fuel‐efficient vehicles) (Camilleri & Larrick ) and applying decision‐aiding techniques to find a balance between long‐term coastal ecosystem conservation and short‐term coastal development under rising sea levels (Mills et al. ). However, explicitly testing how these tools solve temporal mismatches within conservation contexts has received less attention.…”
Section: Synthesis and Prospectusmentioning
confidence: 99%
“…We identified a set of behavioral tools aimed at resolving time-scale challenges in decision making and suggested that many management challenges could be resolved if the right time-scale issues were identified and appropriate behavioral solutions employed to either change the way individuals perceive and value time or alter the consequences of (often short-sighted) behavior. Many of the tools we described have been tested in environmental contexts (e.g., using large-magnitude, broad-bracket frames to increase the attractiveness of fuel-efficient vehicles) (Camilleri & Larrick 2014) and applying decision-aiding techniques to find a balance between long-term coastal ecosystem conservation and short-term coastal development under rising sea levels (Mills et al 2014). However, explicitly testing how these tools solve temporal mismatches within conservation contexts has received less attention.…”
Section: Synthesis and Prospectusmentioning
confidence: 99%
“…for urban use) (Mills et al 2014). Whilst the human element is undoubtedly important, it is vital that strategies to preserve wetlands under climate change are considered alongside anthropocentric impacts in order to conserve species and ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…We extended the approach used by Ando and Mallory (2012a) which can result in a high opportunity cost in setting aside land to allow for wetland migration (Mills et al 2014, Runting et al 2017b. Within this case study we aim to: (i) determine the risk-return trade-offs by adapting Modern Portfolio Theory to conservation planning; (ii) compare scenario-based planning strategies to this approach; and (iii) determine the trade-offs among different conservation objectives, and how these are altered by risk.…”
Section: Introductionmentioning
confidence: 99%